The Business Environment - Adrian Palmer; Bob Hartley (Great Britain McGraw-Hill Professional Publishing, 2011)
The seventh edition of The Business Environment has been perfectly tailored to cover the core topics that will be studied on an introductory Business Environment module. This fully updated new edition provides comprehensive coverage of the varying factors that make up the business environment, with a particular focus on how these factors impact business organisations and the decisions organisations make. Key Features: Up-to-date coverage The business environment continues to evolve, and this new edition takes on board recent issues including: The after-effects of the 'credit crunch' The emerging economic power of China, India and Brazil Data security and privacy Business ethics Cultural identity Climate change Real life examples New opening vignettes introduce the main topic and show the business environment in real life. In addition, the book contains a wealth of shorter and longer case studies featuring companies such as Google, Amazon and Virgin Trains. Pedagogy Clearly written and user friendly, the book boasts a full range of learning tools which include: Learning Objectives, Thinking Around the Subject boxes, Review Questions, and Activities
Keywords: Business; Textbooks; Business Enterprise (BIN1071-N)